Immune Regulatory Cells in Umbilical Cord Blood and Their Potential Roles in Transplantation Tolerance - Kim, Young-June (2010)
Umbilical cord blood (UCB) is a source of primitive hematopoietic stem (HSC) and progenitor cells, that served as an alternative to bone marrow (BM) for effective transplantation therapy. Success of HSC transplantation (HSCT) is limited in part by graft-versus-host disease (GVHD), graft rejection and delayed immune reconstitution, which all relate to immunological complications. GVHD after UCB transplantation is lower compared to that of BM HSCT. This may relate to the tolerogenic nature of T cells, mononuclear cells (MNCs) and especially immune regulatory cells existing in UCB. UCB contains limiting numbers of HSC or CD34(+) cell dose for adult patients resulting in delayed engraftment after UCB transplantation (UCBT). This needs to be improved for optimal transplantation outcomes. Approaches have been undertaken to promote HSC engraftment, including co-infusion of multiple units of UCB cells. These new methods however added additional immunological complications. Herein, we describe current knowledge on features of UCB immune cells, including regulatory T cells (Tregs) and mesenchymal stem/stromal cells (MSCs) and their potential future usage to reduce GVHD.